Effectiveness of the 10-Valent Pneumococcal Nontypeable Haemophilus influenzae Protein D–Conjugated Vaccine (PHiD-CV) Against Carriage and Acute Otitis Media—A Double-Blind Randomized Clinical Trial in Finland. (28th April 2016) - Vesikari, Timo; Forsten, Aino; Seppä, Ilkka; Kaijalainen, Tarja; Puumalainen, Taneli; Soininen, Anu; Traskine, Magali; Lommel, Patricia; Schoonbroodt, Sonia; Hezareh, Marjan; Moreira, Marta; Borys, Dorota; et al.
Abstract : After administering the 10-valent pneumococcal polysaccharide nontypeable Haemophilus influenzae protein D–conjugated vaccine (PHiD-CV) to children aged 2–18 months, we observed a reduction in vaccine-type nasopharyngeal carriage, resulting in a reduction of overall pneumococcal nasopharyngeal carriage, which may be important for indirect vaccine effects. We noted a trend toward reduction of acute otitis media. Background: This trial (ClinicalTrials.gov identifier NCT00839254), nested within a cluster-randomized double-blind invasive pneumococcal disease effectiveness study in Finland (ClinicalTrials.gov identifier NCT00861380), assessed the effectiveness of the 10-valent pneumococcal polysaccharide nontypeable Haemophilus influenzae protein D–conjugated vaccine (PHiD-CV or PCV10) against bacterial nasopharyngeal carriage and acute otitis media (AOM). Methods: Infants (aged 6 weeks to 6 months) received the PHiD-CV or a control vaccine (hepatitis B) (schedule 3+1 or 2+1). Nasopharyngeal swabs were collected at 4 time points post-vaccination from all of the infants and at pre-vaccination from a subset. Parent-reported physician-diagnosed AOM was assessed from first vaccination until last contact (mean follow-up, 18 months). Vaccine effectiveness (VE) was derived as (1 – relative risk)*100, accounting for cluster design in AOM analysis. Significant VE was assessed descriptively (positive lower limit of the non-adjusted 95% confidence interval [CI]). Results: The vaccinated cohort included 5093 infants for carriage assessment and 4117 infants for AOM assessment. Both schedules decreased vaccine-serotype carriage, with a trend toward a lesser effect from the 2+1 schedule ( VE across timpoints 19%–56% [3+1] and 1%–38% [2+1]). Trends toward reduced pneumococcal carriage (predominantly vaccine serotypes 6B, 14, 19F, and 23F), decreased carriage of vaccine-related serotype 19A, and small increases at later time points (ages 14–15 months) in non–vaccine-serotype carriage were observed. No effects on nontypeable Haemophilus influenzae, Staphylococcus aureus, or Moraxella catarrhalis carriage were observed. There were non-significant trends toward a reduction in the number of infants reporting AOM episodes (VE 3+1: 6.1% [95% CI, −2.7% to 14.1%] and 2+1: 7.4% [−2.8% to 16.6%]) and all AOM episodes (VE 3+1: 2.8% [−9.5% to 13.9%] and 2+1: 10.2% [−4.1% to 22.9%]). PHiD-CV was immunogenic and had an acceptable safety profile. Conclusions: We observed reduced vaccine-type pneumococcal carriage, a limited increase in non–vaccine-type carriage, and a trend toward AOM reduction.